ALGORITMA LEBAH, SOLUSI METAHEURISTIK DALAM PENEMUAN NILAI OPTIMAL PADA VARIABEL ALAT INDUSTRI - Ginda Maruli Andi Siregar; Novianda; Nurul Fadillah (Universitas Samudra, 2023)
Heavy equipment or industrial machines have components that involve many variables. The performance of industrial heavy equipment depends on calculating the size of each component so that the machine works optimally. Determining the optimum value of machine component variables is needed so that the machine or industrial equipment can work optimally. The study carried out was to find the optimum variable values ​​for machines or industrial tools using a numerical-computational approach using the bee algorithm. The effectiveness and efficiency of the algorithm will be compared with other methods. The research uses a quantitative approach and is analyzed with statistical descriptions. Based on the results of this research, it is hoped that it can provide a reference for users of industrial equipment in obtaining optimum values. For researchers with similar topics, provides a reference for the application of the bee algorithm in determining function optimization values.